Pelatihan Manajemen Skit Untuk Jemaat Gereja Kristus Yesus Serpong - Gandadinata Thamrin (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2020)
Religious activities such as Christmas and Easter celebrations in the church often use drama performances in delivering spiritual messages to the congregation, spiritual messages in the form of short plays or called skits are more easily accepted by adults and children so that the messages conveyed can be absorbed by the whole church. This was felt to be a necessity for the church to prepare talented, skilled and skilled human resources (HR) in making this short drama so that the leaders and committee of the Church requested training from Pelita Harapan University, Karawaci to give a workshop on